Hubungan Antara Pemilihan Makanan,Frekuensi Diet Bebas Gluten Bebas Kasein Dengan Perilaku Hiperaktif Anak AutisDi Sekolah Luar Biasa Negeri Semarang - Yulianti, Diah Asih; , Ririn Yuliati, S.Si.T., M.Si; , Luluk Ria Rakhma, S.Gz., M.Gizi (2016)
Introduction: One of the efforts to minimize the incidence of autism behavior is avoiding foods that contain gluten and casein because there is a hipermeability in the intestinal mucosa of an autism, resulting in two types of protein are difficult to digest and will from a substance called peptides. Gluten peptides produce gluteomorphin or gliadimorphin and casein peptide from caseomorphin. both of these substances can affect the central nervous system, resulting a behavioral disorders. Objective : The purpose of the study to determine the correlation between selection food, frequency of gluten free casein free diet with hyperactive behavior of children with autism. Research Methods: Cross-sectional study design. The total samples of 26 subjects were selected by total sampling. Data of selection food using the questionnaire, frequency of gluten free casein free diet were measured by FFQ, and hyperactive behavior were measured by DSM IV that has been modified using CARS (Childhood Autism Rating Scale ). Data was analyzed with Rank Spearman correlation. Results: As much 61,5% of food for an autistic child still less. The entire (100%) of the subject in this research is still consume foods that contain gluten and casein. Most of the subject experience problems behavior, as much as 38,5% experience problems behavior hyperactive appared rare. The result of bivariat shows that there is selection of food with the behavior of this hyperactive (p=0,000; r =-0,701). There is a frequency of gluten free casein free diet with the behavior of his hyperactivity (p=0,000, r=0,939). Conclusion: More a lot of food a source of gluten and the source casein consumed the more often the behavior of his hyperactive emerged. Suggestion: Needs to be done guidance for parents about the choice of good food for autistic children.